SURGICAL CORRECTION OF INSUFFICIENCY OF CEREBRAL BLOOD FLOW AT THE ATHEROSCLEROSIS OF EXTRACEREBRAL ARTERIES - V. F. Negrey (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
There is more than 1 million people who have had a stroke in Russia; the third part of these people are of working age, and only every fourth patient returned to job. This article discusses one of the most effective methods of stroke prevention - the procedure of carotid endarterectomy. We performed 468 reconstructive operations in 448 patients. 65 % (305) of surgeries were open carotid endarterectomies. In other cases, operations of prosthetics or blood flow switching between extracerebral arteries (ECA) (163) were carried out. Short-term results of reconstructive operations showed that 96 % of outcomes were positive. Perioperative mortality at operations made 1.06 %. The general complications made 4.5 %, minor complications were observed in 21 patients (4.4 %). The five years survival rate of patients operated on ECA made 86 %, the main cause of death in recent follow-up period was a cardiac pathology (58 %), brain disorders made 15 %. Among dominating risk factors are coronary heart disease, previous transient ischemic attacks and residual neurologic impairment.